Epidemiology of hepatitis C virus in Iran - Taherkhani, Reza (World J Gastroenterol, 2015)
In Iran, the prevalence of hepatitis C virus (HCV) infection is relatively low according to the population-based epidemiological studies. However, the epidemiology of HCV is changing and the rate of HCV infection is increasing due to the growth in the number of injecting drug users in the society. In addition, a shift has occurred in the distribution pattern of HCV genotypes among HCV-infected patients in Iran. Genotype 1a is the most prevalent genotype in Iran, but in recent years, an increase in the frequency of 3a and a decrease in 1a and 1b have been reported. These variations in the epidemiology of HCV reflect differences in the routes of transmission, status of public health, lifestyles, and risk factors in different groups and geographic regions of Iran. Health policy makers should consider these differences to establish better strategies for control and prevention of HCV infection. Therefore, this review was conducted to present a clear view regarding the current epidemiology of HCV infection in Iran.